Quality adjusted life year gains associated with administration of recombinant tissue-type plasminogen activator for treatment of acute ischemic stroke: 1998–2011. Issue 2 (February 2016) - Lubeck, Deborah P; Danese, Mark D; Duryea, Jennifer; Halperin, Marc; Tayama, Darren; Yu, Elaine; Lalla, Deepa; Grotta, James C
Background: Intravenous recombinant tissue-type plasminogen activator (r-tPA) is an approved treatment for select patients with acute ischemic stroke (AIS). Data indicate r-tPA improves functional outcome three months after AIS compared with placebo. This study models the increase in quality adjusted life years (QALYs) associated with r-tPA compared with similar patients not treated with r-tPA. Methods: Hospital discharge data for AIS and r-tPA were obtained from the Nationwide Inpatient Sample from 1998 to 2011. Discharge location (home, rehabilitation, long-term care, death) was mapped to modified Rankin Scale (mRS) scores based on National Institute of Neurological Disorders and Stroke (NINDS) Study Group Part 1 and 2 clinical studies. The mRS scores were mapped to relative risk of death and QALYs obtained from the literature. The model estimated expected survival and QALYs by age, gender and mRS for patients receiving r-tPA. Life expectancy and QALYs for patients not receiving r-tPA were estimated based on discharge location and mRS for placebo patients in the NINDS study. Results: AIS discharges declined from over 635, 000 in 1998 to over 593, 000 in 2011. A total of 183, 235 patients received r-tPA. Utilization of r-tPA increased from 1% of AIS patients in 1998 to over 4% in 2011. Estimated projections for QALYs gained from utilization of r-tPA to QALYS without r-tPA were just under 240, 000 for the 13 years and with no discounting, and just over 165, 000 assuming 3% annual discounting. In the most conservative scenario, assuming no difference in proportional discharge status (i.e. patients not treated with r-tPA are discharged in the same manner as r-tPA patients), the estimated life years gained are approximately 35, 000 and QALYS gained are approximately 90, 000. Conclusions: r-tPA for AIS has resulted in estimated gains in quality-adjusted life years due to reduction in disability and improvement in functioning since its introduction in 1998.